Location-Specific Association Between Cerebral Microbleeds and Arterial Pulsatility - Chou, Kun-Hsien; Wang, Pei-Ning; Peng, Li-Ning; Liu, Li-Kuo; Lee, Wei-Ju; Chen, Liang-Kung; Lin, Ching-Po; Chung, Chih-Ping (Frontiers in Neurology, 2019)
Objective: Increased arterial pulsatility index (API), usually representative of distal vascular resistance, have been linked to cerebral small vessel disease. However, their relationship with cerebral microbleeds (CMBs) is less studied. The present study aimed to evaluate the relationship between CMBs and API. Methods: We cross-sectionally evaluated participants from a non-clinical stroke, non-demented community-based population. APIs of cervical internal carotid and vertebral arteries were measured by ultrasonography. CMBs were assessed by susceptibility-weighted-imaging on 3T magnetic resonance imaging. Subjects were classified according to CMB locations: deep/infratentorial (DI) or strictly lobar (SL) CMB groups. DI-CMB group also included subjects with simultaneous lobar CMBs. Results: Of the 681 subjects [62.2 (8.4) years, 43.5% men] included, CMBs were found in 92 (13.5%) subjects: 57 (8.4%) with DI-CMB and 35 (5.1%) with SL-CMB. The results showed that CMB location influenced their association with API. DI-CMB was significantly associated with elevated API of internal carotid arteries (β=0.031; 95% confidence interval = 0.002-0.059; P=0.03) while SL-CMB was significantly associated with elevated API of vertebral arteries (β=0.050; 95% confidence interval=0.006-0.094; P=0.025) in multivariate analyses adjusting for age, sex, cardiovascular risk factors, white matter hyperintensities and lacunes. Conclusion: Our study again emphasizes (1) the association between API and cerebral small vessel disease and (2) the pathogenic differences between DI- and SL-CMBs. Our results lead to the postulation that in the presence of CMBs without clinical dysfunction yet, insidious small vascular disorders might already occur with corresponding topography.